2021
DOI: 10.3390/nu13082562
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Football Practice on Nutritional Status and Body Composition in Children: A Systematic Review and Meta-Analysis

Abstract: Dietary patterns, exercise, sport, and physical activity have been shown to improve body composition in children. This systematic review with meta-analysis analyzed the effects of practicing football on body composition (fat mass, lean body mass, and bone mineral content) in children. An initial search in PubMed, Web of Science, and SPORTDiscus was carried out in April 2021 to identify relevant articles. Inclusion criteria required children up to 12 years of age with a minimum football intervention duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The emergence of modern football teaching methods such as team cooperation provides an opportunity for the large-scale development of new football courses in colleges and universities. Intelligence has become an important feature of China's current football training system [ 2 ]. At present, although the existing football training system provides a large number of football training methods, it is difficult for players to choose targeted football header shooting training methods according to their own strength structure and biological characteristics in the training process of header shooting and can not achieve the optimal football actual combat effect [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of modern football teaching methods such as team cooperation provides an opportunity for the large-scale development of new football courses in colleges and universities. Intelligence has become an important feature of China's current football training system [ 2 ]. At present, although the existing football training system provides a large number of football training methods, it is difficult for players to choose targeted football header shooting training methods according to their own strength structure and biological characteristics in the training process of header shooting and can not achieve the optimal football actual combat effect [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…After 8 months, soccer players showed a decrease of nearly 1.5% in FM%, while controls presented a decline of 1.8% [23]. The literature underlines that soccer training is associated with benefits to body composition, contributing to the decrease in FM% and increase in fat-free mass [33]. In youth, the aerobic demands of soccer average between 70 and 90% of their maximum heart rate, leading to high-fat loss compared with other sports activities with lower intensity levels [34].…”
Section: Discussionmentioning
confidence: 95%
“…Although most children play soccer recreationally, the number of them who are federated from a very young age by joining a professional club has increased notably [25,26]. It is well known that practicing soccer has beneficial effects on numerous health parameters of children and adolescents [27][28][29]. In this sense, a recent study has demonstrated that U12 male soccer players had better exercise capacity, lower resting heart rate, and higher muscle mass than children that do not play soccer [30,31].…”
Section: Discussionmentioning
confidence: 99%